Placement of Specialist Physicians in Indonesia’s Primary Health Centers: Policy Challenges and Reconstruction Strategies - Ramlan, Ramlan; Hoesein, Zainal Arifin; Barthos, Megawati (International Journal of Business, Law, and Education, 2026)
Community Health Centers (Pusat Kesehatan Masyarakat, or Puskesmas), as primary healthcare facilities, play a strategic role as gatekeepers within Indonesia’s national health system. However, the regulatory framework governing the placement of specialist physicians in Puskesmas has not been explicitly accommodated in existing health policies. This study aims to analyze the legal framework for the placement of specialist physicians in Puskesmas, identify structural, juridical, and implementation-related constraints, and formulate directions for a more adaptive and equitable policy reconstruction. This research employs a normative-empirical legal approach using qualitative methods. Data were collected through interviews with key stakeholders in the Special Capital Region of Jakarta (DKI Jakarta) and through a review of relevant legislation, policy documents, and scholarly literature. The data were analyzed using a descriptive-analytical approach. The findings reveal that the placement of specialist physicians in Puskesmas faces systemic challenges, including regulatory gaps, policy ambiguity, limited resources, and the absence of a coherent policy architecture to support the equitable distribution of medical personnel. Nevertheless, empirical evidence indicates that the presence of specialist physicians contributes significantly to improving diagnostic quality, enhancing the efficiency of the referral system, and strengthening public trust in primary healthcare services in Indonesia.